The genome of the Java medaka (Oryzias javanicus): Potential for its use in marine molecular ecotoxicology. (May 2020) - Lee, Bo-Young; Park, Jun Chul; Kim, Min-Sub; Choi, Beom-Soon; Kim, Duck-Hyun; Lim, Jong-Sung; Yum, Seungshic; Hwang, Un-Ki; Nah, Gyoung Ju; Lee, Jae-Seong
Abstract: The Java medaka ( Oryzias javanicus ) is distributed in tropical brackish water and is considered as an ecotoxicological experimental organism for assessing diverse pollutions and global climate change effects in the ocean. In this study, we sequenced and assembled the genome of O. javanicus using the Oxford Nanopore technique and anchored the scaffolds to the 24 genetic linkage map of a sister species Oryzias melastigma . The assembled genome consisted of 773 scaffolds including 24 LG-based scaffolds, and the estimated genome length was 846.3 Mb (N50 = 19.3 Mb), containing 24, 498 genes. As detoxification processes are crucial in aquatic organisms, antioxidant-related genes including glutathione S -transferases, superoxide dismutase, catalase, and glutathione peroxidase were identified in this study. In the genome of O. javanicus, a total of 21 GST s, 4 SOD s, 1 CAT, and 7 GPx s were identified and showed high similarities between sister species O. melastigma and Oryzias latipes . In addition, despite having 8 classes of cytosolic GSTs family, medaka showed no presence of GST pi and sigma classes, which are predominantly found in carp and salmon, but not in neoteleostei. This study adds another set to genome-library of Oryzias spp. and is a useful resource for better understanding of the molecular ecotoxicology. Highlights: The total length of the Oryzias javanicus is 846.3 Mb with N50 = 19.3 Mb. The total number of scaffolds are 773 including 24 LGs The total number of GST s, GPx s, CAT, and SOD s are 21, 7, 1, and 4, respectively. Pi and sigma GST classes were absent in O. javanicus and Oryzias spp.